Carbon exergy tax applied to biomass integrated gasification combined cycle in sugarcane industry - Fonseca Filho, Valdi Freire da; Matelli, Jose Alexandre [UNESP]; Perrella Balestieri, Jose Antonio [UNESP] (Elsevier B.V., 2016)
The development of technologies based on energy renewable sources is increasing worldwide in order to diversify the energy mix and satisfy the rigorous environmental legislation and international agreements to reduce pollutant emission. Considering specific characteristics of biofuels available in Brazil, studies regarding such technologies should be carried out aiming energy mix diversification. Several technologies for power generation from biomass have been presented in the technical literature, and plants with BIGCC (biomass integrated gasification combined cycle) emerge as a major technological innovation. By obtaining a fuel rich in hydrogen from solid biomass gasification, BIGCC presents higher overall process efficiency than direct burning of the solid fuel in conventional boilers. The objective of this paper is to develop a thermodynamic and chemical equilibrium model of a BIGCC configuration for sugarcane bagasse. The model embodies exergetic cost and CO2 emission analyses through the method of CET (carbon exergy tax). An exergetic penalty comparison between the BIGCC technology (with and without CO2 capture and sequestration), a natural gas combined cycle and the traditional steam cycle of sugarcane sector is then presented. It is verified that the BIGCC configuration with CO2 capture and sequestration presents technical and environmental advantages when compared to traditional technology. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gasification; Biomass; IGCC; Carbon exergy tax; CO2 emission